(untitled) (Materiali di Estetica. Terza serie, 2017)
Some short philosophical reflections on some crucial and emerging themes of Gadda’s work. We leave from Gadda to return to Leibniz and return to philosophical Milan at the beginning of the twentieth century, with Piero Martinetti. The short trip has an exceptional Virgil: Dante Isella, which helps to blend Gadda’s work critically.